Antimicrobial and cytotoxic properties of actinobacteria associated with a stony coral Fungia sp. from Karimunjawa National Park, Indonesia - Mada Triandala Sibero, Evan Hansel Frederick, Diah Permata Wijayanti, Dwi Haryanti, Anggun Puspitarini Siswanto, Yasuhiro Igarashi (Journal of Applied Pharmaceutical Science, 2024)
Coral-associated actinobacteria are a prospective resource for obtaining novel bioactive compounds with various biological activities. This research was carried out to isolate and identify coral-associated actinobacteria from Karimunjawa National Park, to study their potential as antimicrobial and cytotoxic agents, to obtain the most prospective actinobacteria with its suitable media for bioactive production, and to characterize the secondary metabolites from the prospective extracts. Analysis of the 16S rRNA gene sequence revealed that the bacteria consisted of Proteobacteria (53.84%), Actinobacteria (30.76%), and Firmicutes (15.40%). Four actinobacteria isolates, namely, Streptomyces pluripotens CM4, Streptomyces ardesiacus CM11, Micrococcus flavus CM13, and Gordonia hongkongensis CM20, were cultivated in A3, A11, and A16 media to produce secondary metabolites. The bioassay screening discovered that S. pluripotens CM4 and S. ardesiacus CM11 exhibited antibacterial and cytotoxicity potential. However, it was noted that extract of S. ardesiacus CM11 from A11 medium was able to inhibit all bacterial pathogens with a range of minimum inhibitory concentration value of 7.81–15.62 μg/ml, while the range of minimum bactericidal concentration value of 7.81–62.50 μg/ml. In addition, the lowest IC50 value for cytotoxicity was exhibited by S. ardesiacus CM11 from the A3 medium (4.43 ± 2.85 μg/ml).
Keywords: Actinobacteria, antimicrobial, coral, cytotoxicity, Streptomyces